Correlation Between Vitamin D3 Levels, Autoantibodies, and Antibody-Related Diseases in Patients with Hashimoto's Thyroiditis - Ali Saad Kadhim; Abdullah Salim Al-Karawi (Turkish Journal of Immunology)
Objective: Hashimoto's thyroiditis (HT) is a common autoantibodies condition that impact on the thyroid gland. In this disorder, several autoantibodies play an essential role in the dysfunction of the thyroid, including the metabolism of 1,25-dihydroxyvitamin D3 (1,25 VitD3)-XP, and leading to contributed to the development of related autoimmune diseases. The aim of current study to explore the important correlation between 1,25 VitD3 deficiency and specific types of autoantibodies in the patients. Materials and Methods: The current involved 150 male's patients, aged 25-50 years, who were compared with same numbers and aged of as healthy controls. Various biomarkers to thyroid gland were measured, including thyroid -stimulating hormone (TSH), free thyroxine (T4), free triiodothyronine (T3). In additionally, anti-thyroid peroxidase (TPO), thyroglobulin (TG), TSH receptor antibodies (TRAbs) and 1,25VitD3 were measured. These biomarkers were measured by the electrochemiluminescence immunoassay technique (ECL). Furthermore, the level of antibodies against VitD3, extractable nuclear antigens m immunoglobulin G4 related disease (IgG4-RD), and glycoprotein 120 were assessed by IDS-system. Results: This study indicated that blood group B was most commonly associated with HT. Moreover, the concentration of the 1,25 VitD3 was significantly lower in the patient group compared to the control, with level of 3.5 +- 0.1, 35.9 +- 0.3 ng/mL, respectively. Furthermore, an inverse positive correlation in the increased concentrations of TRAbs, TG, and TPO (r=-0.98, -0.66, -0.75) autoantibodies and the low levels of 1,25 VitD3 were detected. Likewise, a strong direct correlation (r=+0.98) was observed in the increased concentrations of both anti-TSH and anti-VitD3. Finally, IgG4-RD had a significantly positive association with the concentrations of 1,25 VitD3-XP, and TSH in patients with a highly significant difference (p<0.001). Conclusion: The findings suggested a significant positive correlation between increased levels of autoantibodies, antibody-related diseases, and low 1,25 VitD3 levels.